2012
DOI: 10.1080/13554794.2012.732087
|View full text |Cite
|
Sign up to set email alerts
|

Agraphia in patients with frontotemporal dementia and parkinsonism linked to chromosome 17 with P301LMAPTmutation: dysexecutive, aphasic, apraxic or spatial phenomenon?

Abstract: Objectives Patients with frontotemporal dementia and parkinsonism linked to chromosome 17 (FTDP-17) may be agraphic. The study aimed at characterizing agraphia in individuals with a P301L MAPT mutation. Methods Two pairs of siblings with FTDP-17 were longitudinally examined for agraphia in relation to language and cognitive deficits. Results All patients presented with dysexecutive agraphia. In addition, in the first pair of siblings one sibling demonstrated spatial agraphia with less pronounced allographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
0
10
1
Order By: Relevance
“…Of all 31 cases that we reviewed, only one case (3.2%; Case 20 in Table ) presented with apathy as the sole initial symptom: this was a male patient who initially developed apathy without other obvious behavioral changes at the age of 49 years. However, unlike our case, depression characterized by suicidal ideation developed 1 year later . At 55 years, he developed L‐dopa‐responsive parkinsonism (unilateral resting tremor and hypomimia).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Of all 31 cases that we reviewed, only one case (3.2%; Case 20 in Table ) presented with apathy as the sole initial symptom: this was a male patient who initially developed apathy without other obvious behavioral changes at the age of 49 years. However, unlike our case, depression characterized by suicidal ideation developed 1 year later . At 55 years, he developed L‐dopa‐responsive parkinsonism (unilateral resting tremor and hypomimia).…”
Section: Discussioncontrasting
confidence: 56%
“…The most frequently noted initial symptom was personality change (13 cases, 41.9%). Behavioral change was the second most common (10 cases, 32.3%, and personality change was also noted in eight of these 10 cases) . The third most common was memory impairment, being observed in six cases (19.4%) .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, clear differences between AD patients and healthy control individuals have been found for visuomotor task measures demonstrating large effect size deficits by AD patients especially with visuomotor task progression through its varying conditions [51]. Sitek et al [52] have observed dysgraphia, primarily dysexecutive agraphia, in patients with frontotemporal dementia and parkinsonism linked to chromosome 17 (FTDP-17). Patients presenting 'dysexecutive' agraphia show not only difficulties in maintaining the effort inherent to writing but appear to lack the ability to organize their thoughts for expression in the written text.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, clear differences between AD patients and healthy control individuals have been found for visuomotor task measures demonstrating large effect size deficits by AD patients especially with visuomotor task progression through its varying conditions [49]. Sitek et al (2014) [50] have observed dysgraphia, primarily 'dysexecutive. agraphia, in patients with frontotemporal dementia and parkinsonism linked to chromosome 17 (FTDP-17).…”
Section: Discussionmentioning
confidence: 99%